Search for the electromagnetic properties of the neutrinos at the HL-LHC and the FCC-hh - M. Köksal; A. Senol; H. Denizli (Physics Letters B, 2023)
The νν¯γγ couplings parametrized with the non-standard dimension-seven operators defined by the Effective Field Theory framework are investigated through the process pp→νν¯γ at the High Luminosity-LHC and the Future Circular proton-proton Collider. The effective Lagrangian of νν¯γγ couplings is implemented into FeynRules to generate a UFO module inserted into Madgraph to generate both background and signal events. These events are then passed through Pythia 8 for parton showering and Delphes to include realistic detector effects. The sensitivities on νν¯γγ couplings are obtained at 95% confidence level. We show that the analysis of the signal emerging from the process pp→νν¯γ allows to improve constraints on νν¯γγ couplings given by the LEP collaboration.